PENGARUH PENEKANAN KAIDAH IMLA DALAM KEMAMPUAN MENULIS BAHASA ARAB (IMLA') - Mulya Nugraha, Rahmat; Bahar, Rosid; Siti Fatimah , Titim (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2024)
This research aims to investigate the influence of applying the rules of Imla in teaching Arabic writing skills at SMAT Riyadlul Ulum Wadda'wah. The main problem backgrounding this research is the lack of effectiveness of Imla teaching in that school. The research method employed is an experiment with a pre-posttest control group design. Two groups of students were sampled, with one group receiving Imla teaching based on established rules, while the control group received conventional teaching. Data were collected through Arabic writing tests before and after the treatment. The research results indicate that the significance value α = 0.67 > 0.05, proving that the application of Imla rules significantly improves the Arabic writing skills of students at SMAT Riyadlul Ulum Wadda'wah compared to the control group. These findings suggest that the use of Imla rules in Arabic language teaching has great potential to enhance learning effectiveness in the school. The implications of this research are that teaching Imla with appropriate methods can be a solution to addressing the lack of Arabic writing skills at the high school level, providing guidance for teachers and schools in improving Arabic language teaching methods, and promoting the use of Imla as an effective tool in the learning process.